Perubahan Makna Perayaan Maulid Nabi Muhammad SAW bagi Masyarakat Kelurahan Dasan Agung Kecamatan Selaparang Kota Mataram - Khaerunnisa Khaerunnisa; Ika Wijayanti; Siti Nurjannah (Prodi Sosiologi Universitas Mataram, 2019)
The Prophet's Maulid celebration is one of the celebrations of Muslims day. Almost all over Lombok always commemorates the celebration of the Prophet's Maulid with joy. One of theareas in Mataram city that has uniqueness on the celebration of the Prophet's Maulid is Kelurahan Dasan Agung, the community has a unique ritual in the celebration of the Prophet Maulid because of the procession and celebrations that are packed such as parties equipped with Music. This uniqueness is a form of cultural change in the celebration of the Maulid of the Prophet Muhammad. The research methods used are qualitative research. This is because the research aims to understand the linkages caused by the change of meaning and social change of culture that occurred in the celebration of the Prophet Maulid. The data required in this study are primary data such as interviews and documentation results, as well as secondary data such as Kelurahan profiles, citizen documentation, and community Journal Records. Data collection techniques in four ways are field and data observation, document tracing, interviews, and documentation. The Prophet's Maulid celebration for the people of Dasan Agung still has the same usage of the Prophet's Maulid celebration in general. However, on some series of celebrations of the Prophet's Mawlid in Kelurahan Dasan Agung have changed. One of the series of celebrations of the Prophet Muhammad SAW that is quite a lot of change is in Praje. Praje is one of the series of the Mawlid celebration of the Prophet Muhammad SAW in the village of Dasan Agung who has existed since the first time. The music accompanying the Praje also underwent a change in the early 80 's from religious music to Dangdut music, until now using a variety of music.